Os materiais e as técnicas usados numa escultura barroca, do Museu de Santa Maria de Lamas, representando São Domingos - Barata, Carolina (2011)
A polychrome wooden sculpture from the Museum of Santa Maria de Lamas (Northern Portugal), representing the image of Saint Dominic, produced in the first half of the 18th century, was studied for the identification of the materials and techniques employed in its fine modelling. Radiography was used for the study of the construction details of the wooden support, optical microscopy (OM) and polarized light microscopy (PLM) for the characterization of the paint layers and energy dispersive X-ray spectrometry (EDXRF), Fourier transform infrared spectroscopy (FTIR) and microchemical tests for the identification of pigments and fillers.The identified materials were common to the period when the sculpture was made: gypsum, gold leaf, bole,white lead, brown ochre, vermillion, a black pigment made of carbon (possibly mixed with verdigris, used as a drier), a red lake and a calcium compound used as filler. However, regarding the techniques employed, and probably due to economic reasons, it seems that the recommended practice in art treatises and working contracts was not completely followed in what concerns the ground layers. Similar reasons appear to have caused the use of white lead mixed with a calcium compound, as a filler, in the less expressive areas, and should explain the fact that the estofado techniques (simulation of brocaded vestment) have been limited to the visible areas at the front.